2014
DOI: 10.1080/14786419.2014.921684
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry analysis of icariside II metabolites in rats

Abstract: The possible metabolic pathways of icariside II were proposed. An ultra-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry method was used for analysing the faecal, bile, plasma and urine samples of rats administrated with icariside II. In all, 27 metabolites were identified in the biosamples. Of these, 20, including F1-F12, D3, D4, D6, D7-D9 and M3, M4, were, to our knowledge, reported for the first time. The results indicated that icariside II was metabolised via desugarisation, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We also found that IS down-regulated cFLIP partially through inhibition of NF-κB nuclear translocation (summarized in Figure 6E). The anti-inflammatory, anticancer activities and the pharmacokinetic of IS have been studied [21, 32, 33]. IS might be a promising agent in reversing TRAIL resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that IS down-regulated cFLIP partially through inhibition of NF-κB nuclear translocation (summarized in Figure 6E). The anti-inflammatory, anticancer activities and the pharmacokinetic of IS have been studied [21, 32, 33]. IS might be a promising agent in reversing TRAIL resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the metabolized mainly via desugarisation, dehydrogenation, hydrogenation, hydroxylation, demethylation, glucuronidation, dehydration, and glycosylation pathways in vivo . Specific hydrolysis of 7-O glucoside in the gut lumen and glucuronic acid conjugation in the liver was considered as the main physiologic processes of icariside II (Sun et al, 2014). …”
Section: Components Isolated From Tcms That Target Epidermal Growth Fmentioning
confidence: 99%
“…IT was the structural parent nucleus of ICA and BHG-I, and the glycosylation number of IT, BHG-I, and ICA were 0, 1, 2, respectively (Figure 1). Previous studies revealed that higher concentrations of IT were discovered in rat plasma, urine, and feces after oral administration of ICA or BHG-I (Sun et al, 2014;Sun et al, 2016). Pharmacological studies confirmed that ICA increased bone mass and prevent glucocorticoid-induced apoptosis in osteocytes (Feng et al, 2013;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 97%